Acute Mesenteric Ischemia - Sampoanggoen, Thatnatthanon; Orrapin, Saritphat (Journal of the Association of General Surgeons of Thailand under the Royal of Patronage of HM the King, 2024)
Acute mesenteric ischemia is a condition in which there is a sudden lack of blood flow to the intestines, leading to bowel gangrene, morbidity and mortality. The most common causes include mesenteric arterial embolism, thrombosis, mesenteric venous thrombosis, and non-occlusive mesenteric ischemia. Diagnosis is typically done using computed tomography angiography (CTA), which helps determine the location of pathology and the extent of the ischemia included the complication of mesenteric ischemia. Treatment involves medications to prevent clot propagation and preserve collateral vessel by anticoagulant, fluid replacement, and urgency surgical intervention to restore blood flow and reduce the risk of intestinal loss and mortality. Therefore, physicians and surgeons should have knowledge of both diagnosis and initial treatment options, leading to prompt surgical decision-making for rapid treatment and decreased patient mortality.